"Exploring Tourist Perspectives on Post-Pandemic Tourism in Andhra Pradesh- A Field Study in Kurnool District.” - D. Ramanjulu ,D. Krishnamoorthy (Cuestiones de Fisioterapia, 2025)
The COVID-19 pandemic profoundly disrupted the global tourism industry, reshaping traveller preferences, behaviours, and expectations. This study focuses on understanding post-pandemic tourism through the lens of tourists visiting the Kurnool district in Andhra Pradesh, a region known for its historical, cultural, and natural attractions. Employing a field-based approach, the research captures first-hand perspectives on the conditions in the tourism destinations